2014
DOI: 10.3991/ijet.v9i2.3268
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Classroom vs E-learning in Higher Education: Difference between Students' Behavioral Engagement

Abstract: We discuss traditional classroom, e-learning, behavioral engagement and difference between behavioral engagements in two kind of instruction environment. Results from variance analyses suggest that there is no significant difference between engagements of active learning in different classroom conditions, and there exist significant differences on higher-level learning of innovative and critical thinking. Our findings highlight students' behavioral engagements in two environments have no significant advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 12 publications
5
27
0
3
Order By: Relevance
“…Furthermore, it was found that the more important they felt it to have classmates nearby, the more strongly they believed that watching the videos made a contribution. Based on the literature, it might be that watching together promotes the sense of belonging to a learning community, and eventually contributing to the learning process (Anderson, 2003;Moore & Kearsley, 2005;Li et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that the more important they felt it to have classmates nearby, the more strongly they believed that watching the videos made a contribution. Based on the literature, it might be that watching together promotes the sense of belonging to a learning community, and eventually contributing to the learning process (Anderson, 2003;Moore & Kearsley, 2005;Li et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, the transfer of responsibility for online study to a location away from the classroom promotes a sense of control of the learning process and flexibility in carrying it out, both of which potentially enhancing the student's involvement and motivation (Moore & Kearsley, 2005;Palloff & Pratt, 2011;Subrahmanyam & Šmahel, 2011;Brookfield, 2013;Morse, 2013; Bonk & Kahoo, 2014;Li et al, 2014;Piersol, 2014;Selwyn, 2014). Despite this salutary potential, possible negative implications of self-directed online study, away from the classroom, should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Although online learning has limitations, universities need to adopt it. (Li, Qi, Wang, & Wang, 2014) stated that e-learning facilitates higher levels of learning, better aspects of innovative thinking and critical thinking. (Hattie & Donoghue, 2016) stated that e-learning facilitates higher level learning better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theoretical background of e-learning is modern pedagogical technologies which include the theory of gradual formation of mental action, developmental teaching, problem-based learning, advanced education, learning through play, modular learning, project-based learning and others. The characteristics of e-learning components, criteria-based assessment and future development are studied in the works of Li, Qi, Wang, & Wang (2014); Wang (2014); Batalla, Rimbau, & Serradell (2014).…”
Section: E-learningmentioning
confidence: 99%